Representasi Nilai Perjuangan Film Mungkin Esok atau Nanti Semiotika Charles Sanders Peirce: nilai perjuangan, film, semiotika - Mia, Salmia; Kasmawati, Kasmawati; Aryanti, Aryanti (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2025)
This study aims to analyze the representation of struggle values in the film Mungkin Esok Lusa atau Nanti using Charles Sanders Peirce’s semiotic theory. The research employed a qualitative descriptive method by analyzing 13 selected scenes through the elements of sign, object, and interpretant, as well as identifying types of signs including icons, indexes, and symbols. The results reveal that the film portrays struggle values such as hard work, loyalty, responsibility, morality, spirituality, sacrifice, courage, and national spirit. The meaning of the signs is closely linked to Indonesian cultural values, including politeness, respect for teachers, devotion to parents, simplicity, commitment, honesty, consensus, and maintaining social harmony. The findings show that the film not only presents a romantic drama but also serves as an effective medium to convey moral messages, raise awareness of struggle values, and inspire audiences to apply them in daily life.